A centralized resource for bacterial–fungal interactions research. Issue 5 (May 2023) - Robinson, Aaron; Babinski, Michal; Xu, Yan; Kelliher, Julia; Longley, Reid; Chain, Patrick
Abstract: Research on bacterial-fungal interactions (BFIs) has revealed that fungi and bacteria frequently interact with one another within diverse ecosystems and microbiomes. Assessing the current state of knowledge within the field of BFI research, particularly with respect to what interactions between bacteria and fungi have been previously described, is very challenging and time consuming. This is largely due to a lack of any centralized resource, with reports of BFIs being spread across publications in numerous journals using non-standardized text to describe the relationships. To address this issue, we have developed the BFI Research Portal, a publicly accessible database of previously reported interactions between bacterial and fungal taxa to serve as a centralized resource for the field. Users can query bacterial or fungal taxa to see what members from the other kingdom have been observed as interaction partners. Search results are accompanied by interactive and intuitive visual outputs, and the database is a dynamic resource that will be updated as new BFIs are reported. Highlights: The first public database of published interactions between bacteria and fungi. Database can be queried using bacterial or fungal taxa. Results are presented in interactive and graphical formats for easy interpretation. The database of bacterial-fungal interactions will be continuously updated.